Yoga Therapy Can Reduce Blood Pressure in Hypertension Patients - DOMIANUS NAMUWALI (Poltekkes Kemenkes Kupang, 2017)
Background: Hypertension is an increase in systolic blood pressure above 140 mmHg and diastolic blood pressure above 90 mmHg. Hypertensive disease in Indonesia ranks the most 7 (seven) of the ten CBG's codes at advanced inpatient service levels with 70.128 cases. Hypertension treatment is broadly divided into 2 types namely non-drug treatment (non-pharmacology) and treatment with drugs (pharmacology). Yoga therapy is a non-pharmacology therapy that can help lower blood pressure. This study aims to find out the effect of yoga therapy on reducing the blood pressure of hypertensive patients. Methods: The research method used was a literature review towards research results related to the effect of using yoga therapy to decrease blood pressure in hypertensive patients published in the database of EBSCO, Medline, PubMed and Google Scholar. The selected articles were English published articles from 2004 to 2014 which can be accessed full text in pdf format. Results: The results of this study were 4 articles found in the database showed that there was an effect of yoga therapy in lowering blood pressure of hypertensive patients. Conclusion: There was an effect of yoga therapy on blood pressure reduction of hypertensive patients.